2021
DOI: 10.1001/jamainternmed.2021.3098
|View full text |Cite
|
Sign up to set email alerts
|

The Trial to Reduce Antimicrobial Use in Nursing Home Residents With Alzheimer Disease and Other Dementias (TRAIN-AD)

Abstract: IMPORTANCE Antimicrobials are extensively prescribed to nursing home residents with advanced dementia, often without evidence of infection or consideration of the goals of care.OBJECTIVE To test the effectiveness of a multicomponent intervention to improve the management of suspected urinary tract infections (UTIs) and lower respiratory infections (LRIs) for nursing home residents with advanced dementia. DESIGN, SETTING, AND PARTICIPANTSA cluster randomized clinical trial of 28 Boston-area nursing homes (14 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 60 publications
0
35
0
1
Order By: Relevance
“…The course of Alzheimer's disease is about 5–10 years, and a few patients can survive for more than 10 years. Most of them die from complications such as lung infection, urinary tract infection, and pressure ulcers [ 13 15 ]. Therefore, it is key to identify the hub genes, explore the pathogenesis, and search for the therapeutic targets of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The course of Alzheimer's disease is about 5–10 years, and a few patients can survive for more than 10 years. Most of them die from complications such as lung infection, urinary tract infection, and pressure ulcers [ 13 15 ]. Therefore, it is key to identify the hub genes, explore the pathogenesis, and search for the therapeutic targets of AD.…”
Section: Introductionmentioning
confidence: 99%
“…This similarity might indicate that a vital component of ACP is establishing the nuanced spectrum of options and outcomes, which is counter to practice and regulations in many jurisdictions that mandate goals of care designations with few gradations [ 60 , 61 ]. Finally, a cluster randomised study in 28 American NHs found no effect of an intervention aimed at reducing antibiotic use in residents with severe dementia and suspected infection [ 62 ]. This negative result might reflect an intervention aimed at NH staff and limited to a single clinical issue, whereas the significant reduction in antibiotic use in BABEL may reflect it being an interactive intervention aimed at engaging residents and their proxies in a larger discussion about appropriate goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…The trial began in August 2017 and all data collection was complete by March 1, 2020, with the main findings published elsewhere [ 20 ]. This report leverages implementation data from the 14 NHs in the intervention arm.…”
Section: Methodsmentioning
confidence: 99%
“…Eligible NHs had greater than 60 beds and were located within 60 miles of Boston [ 20 ]. Study information was mailed to senior administrators, who were telephoned one week later by a research team member to solicit their facility's participation, including their agreement to randomize their facility to either the intervention or control arm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation